2022
DOI: 10.1002/1348-9585.12377
|View full text |Cite
|
Sign up to set email alerts
|

Working hours, side work, and depressive symptoms in physicians: A nationwide cross-sectional study in Japan

Abstract: Objectives Long working hours in Japan is a social concern. This is also true for the working hours of physicians, who often do side work in addition to working at their main hospital. New physician work regulations to be implemented in Japan require work‐hour management, including side work. This study examined the association between physicians' overtime and side work hours and their health outcomes. Methods We conducted a cross‐sectional study using data from a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In this study, increased working hours and night shifts were significantly associated with more depression in physicians but not with suicidal ideas. However, other studies reported that increased psychiatric disorders and suicidal ideation were associated with increasing working hours for physicians [ 40 , 64 , 65 ]. The wrong reporting or the smaller sample size may explain the difference in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, increased working hours and night shifts were significantly associated with more depression in physicians but not with suicidal ideas. However, other studies reported that increased psychiatric disorders and suicidal ideation were associated with increasing working hours for physicians [ 40 , 64 , 65 ]. The wrong reporting or the smaller sample size may explain the difference in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a consequence of life disbalance, depression, and loss of hope. Like in medical doctors, where suicide is relatively frequent, mainly in females [37,38], nurses are also exposed to the risk of suicide [39]. This trend was aggravated during the pandemic, when nurses, such as other HCPs, were more to risk to commit suicide [40].…”
Section: Suicide In Nursesmentioning
confidence: 99%
“…Physician overwork is associated with depressive symptoms and suicidal ideation (1) , (2) . The Japan Medical Association (JMA) has been engaged in supporting the health of employed physicians for several years.…”
mentioning
confidence: 99%